Pharmacotherapy of androgenetic alopecia – a literature review - Tyszkiewicz, Marcin; Pożarowska, Kinga; Rosińska, Agata; Orczykowski, Maciej (Journal of Education, Health and Sport, 2022)
INTRODUCTION: Androgenetic alopecia, also known as male pattern baldness, is a common dermatological problem. It manifests as hair thinning and miniaturization of hair follicles. In recent years, knowledge of the risk factors and pathomechanisms of this disease has increased, making treatment more effective. Serious consequences of this condition include reduced quality of life and patient self-esteem. PURPOSE OF THE WORK: The purpose of this paper is to review and discuss selected studies involving agents used in the pharmacotherapy of androgenetic alopecia and to evaluate their safety and efficacy. DESCRIPTION OF THE STATE OF KNOWLEDGE: There are two drugs approved by the Food and Drug Administration (FDA) for the treatment of androgenetic alopecia - oral finasteride 1 mg and 2% or 5% minoxidil solution for topical use. There are also other preparations for external use, such as 0.1% finasteride solution or ketoconaloze shampoo, and for oral use, dutasteride. They seem to be a promising alternative for the treatment of androgenetic alopecia, but require further research. It is possible to use one drug of choice or to use combination therapy to achieve better therapeutic effects. SUMMARY: In order to achieve the best and fastest treatment results, patients should be treated with combination therapy consisting of two or more preparations. To reduce systemic side effects, consider using several topical preparations.